AKIDAH AKHLAK GENERASI DIGITAL OPTIMALISASI SBL BERBASIS FLIPBOOK DI MTSN BANDAR LAMPUNG - Aniesya Octia; Syaiful Anwar; Koderi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a flipbook media Aqidah Akhlak based on the Simulation Based Learning (SBL) learning model and analyze its effectiveness on 8th grade students of MTsN 2 Bandar Lampung. The background of this study is the need for innovative learning media that can increase students' interest and understanding of the Aqidah Akhlak material, considering the challenges of conventional learning which are often less interactive and motivating. By integrating simulations, flipbooks are expected to be able to create a more interesting and contextual learning experience. The research method used is Research and Development (R&D) with ADDIE stages (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 8th grade students of MTsN 2 Bandar Lampung. The effectiveness of the media was measured through a questionnaire involving 126 respondents, with quantitative data analysis using descriptive and inferential statistics. The trial results showed that the SBL-based Aqidah Akhlak flipbook media received positive responses from students and teachers, and met the criteria of validity and practicality. Overall, the development of the SBL-based Aqidah Akhlak flipbook media was proven effective in increasing students' understanding and interest in learning. Quantitative figures show that more than 85% of students responded positively to this media, and there was an average increase in material comprehension scores of 20% after using the flipbook. The implication of this study is the recommendation to use the SBL-based Aqidah Akhlak flipbook media as an innovative and effective learning alternative to improve the quality of Islamic Religious Education learning in schools.